PEMBERDAYAAN ZAKAT PRODUKTIF DALAM PEMBERANTASAN KEMISKINAN - Siti Aminah Chaniago (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2012)
This paper tries to examine the role of zakat in addressing the problem of poverty. Zakah is one of the fundamentals of Islam that has direct economic implications. It requires Muslims to distribute a part of their wealth among the specified heads in order to alleviate poverty and achieve economic emancipation. This institution was able to solve the problems of poverty and extend social services in the classical times. The objective of the paper is to investigate how the zakah institution can be used in the contemporary times to alleviate poverty in Muslim countries.